Fostering Cooperation through the Enhancement of Own Vulnerability - Anita Kopanyi-Peuker; Theo Offerman; Randolph Sloof (Tinbergen Institute, 2012)
We consider the possibility that cooperation in a prisoner's dilemma is fostered by people's voluntarily enhancement of their own vulnerability. The vulnerability of a player determines the effectiveness of possible punishment by the other. In the Gradual mechanism, players may condition their incremental enhancements of their vulnerability on the other's choices. In the Leap mechanism, they unconditionally choose their vulnerability. In our experiment, subjects only learn to cooperate when either one of these mechanisms is allowed. In agreement with theory, subjects aiming for cooperation choose higher vulnerability levels in Gradual than in Leap, which maps into higher mutual cooperation levels.
Keywords: D03; D81; D83; 330; prisoner's dilemma; cooperation; endogenous punishment